Analisis Kekakuan Pada Pelat Baja Galvanil 0.8mm Akibat Pembentukan Dingin Dengan Metode Bead Rolled Variasi Ukuran Dan Bentuk Radius - Avriyansah, Illham; Erwanto, Erwanto (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Cold plate forming process is widely used and needed in manufacturing industries such as automotive industry. One of the cold plate profile forming processes is by plate roll process or often called